Yeast factories for the production of aromatic compounds: from building blocks to plant secondary metabolites. (1st November 2016) - Suástegui, Miguel; Shao, Zengyi
Abstract: The aromatic amino acid biosynthesis pathway is a source to a plethora of commercially relevant chemicals with very diverse industrial applications. Tremendous efforts in microbial engineering have led to the production of compounds ranging from small aromatic molecular building blocks all the way to intricate plant secondary metabolites. Particularly, the yeast Saccharomyces cerevisiae has been a great model organism given its superior capability to heterologously express long metabolic pathways, especially the ones containing cytochrome P450 enzymes. This review contains a collection of state-of-the-art metabolic engineering work devoted towards unraveling the mechanisms for enhancing the flux of carbon into the aromatic pathway. Some of the molecules discussed include the polymer precursor muconic acid, as well as important nutraceuticals (flavonoids and stilbenoids), and opium-derived drugs (benzylisoquinoline alkaloids).